2013
DOI: 10.1784/insi.2012.55.2.84
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and analysing oil condition to generate maintenance savings: a case study in a CNG engine powered urban transport fleet

Abstract: Monitoring and analysing oil condition to generate maintenance savings: a case study in a CNG engine powered urban transport fleet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…There is recent research about its origins and its evolution along ODI, and there are some expectations to find more specific ways to detect oil deterioration point through this parameters [27][28][29] .…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is recent research about its origins and its evolution along ODI, and there are some expectations to find more specific ways to detect oil deterioration point through this parameters [27][28][29] .…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…There is recent research about its origins and its evolution along ODI, and there are some expectations to find more specific ways to detect oil deterioration point through this parameters. [27][28][29] On the other hand, FT-IR has been assessed recently as an analytical technique to detect presence of certain types of additives (due to the presence of characteristic molecular bonds), and some methodologies have been developed to quantify them. 30 In this study, it has been used to quantify the aminic and antiwear additive depletion, using FT-IR spectra methodology measurement procedures based on ASTM D6810 31 and ASTM D6971.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Comparative studies between Diesel and CNG engine oils performance have shown accelerated oil oxidation and higher engine wear rate for some metals such as copper on CNG engines, as a consequence of higher stress suffered by those oils related with higher thermal stress . This situation has been observed on formulations recommended by the own engine manufacturer.…”
Section: Introductionmentioning
confidence: 95%